Pengaruh Manajemen Sumber Daya Manusia terhadap Kuantitas Tenaga Kerja Perusahaan di Perusahaan Bidang Jasa Event Organizer (Studi Kasus PT. BOAK GLOBAL SMARTINDO) - Ramadani, Zulfan; Arnu, Anggi Pasca (Peneliti.net, 2025)
Human Resource Management has become important for Companies where it can influence Company Finance but by managing its People or Workforce. This research uses a case study at PT. BOAK GLOBAL SMARTINDO to find out how Human Resources Management influences the Quantity of its Workforce. This research uses quantitative research methods with a case study approach and is followed by materials including primary, namely internship reports, secondary, namely previous research journals and tertiary materials, namely from the internet and other sources.